2020
DOI: 10.3390/su12062352
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Variables to Predict Autotelic Experience and Enjoyment of Students. Analysis in Function of Environment and Sports Practice

Abstract: The aim of this study was to find out how self-determined motivation, Basic Psychological Needs (BPN) and the perception of support influence autonomy-predicted autotelic experience and enjoyment, and to analyse the differences depending on the geographical location of the centre and whether they lead to the practice of physical activity, extracurricular or not, of 271 learners in physical education from 10 to 12 years (M = 10.94, SD = 0.73). The theoretical framework used was the Self-Determination Theory. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Thus, Orsini et al [ 12 ] postulate that autonomic motivation to engage in academic activities can be enhanced in health education by an early detection of students’ characteristics, as well as by changes in the educational environment. Autonomous motivation can predict an individual’s engagement and performance in both competitive sport and recreational physical activity [ 6 , 13 , 14 , 15 ]. Moreover, motivation can explain participation in and withdrawal from physical exercise during leisure time, in addition to participation in school-based physical education lessons [ 6 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Orsini et al [ 12 ] postulate that autonomic motivation to engage in academic activities can be enhanced in health education by an early detection of students’ characteristics, as well as by changes in the educational environment. Autonomous motivation can predict an individual’s engagement and performance in both competitive sport and recreational physical activity [ 6 , 13 , 14 , 15 ]. Moreover, motivation can explain participation in and withdrawal from physical exercise during leisure time, in addition to participation in school-based physical education lessons [ 6 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the Autotelic experience scores of the low-scoring groups in both the prior knowledge/learning effectiveness were significantly higher than the high-scoring groups. Autotelic experience means that the activity itself offers attractive content to the participants, such as enjoyable experiences and engaging goals (Fong et al, 2015), and in the case of Leyton-Román et al (2020), it was noted that autotelic experience was related to students' participation in the course, such as the presence of group discussions and students' performance in the course. The results show that the active participation of the low achievers in this study was significantly higher in the teaching activities, which also indicates to some extent that the active engagement level of the low achievers can be significantly higher than that of the high achievers, even when the overall students' flow is high.…”
Section: Differences In Flow Between Learners With High and Low Prior...mentioning
confidence: 99%
“…One of the main features of the autotelic experience is that it occurs during an interaction (Asakawa, 2004 ). In fact, during this interaction, consciousness shifts and finds an invisible pull toward the desire to maintain and perpetuate this enjoyable moment (Leyton-Román et al, 2020 ). In this case, the attention exceeds the usual level and increases awareness and sensory attention.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%